Analysis of Islamic Law Accommodation In National Law during the Era of Democratic Transition Government 2001-2004 - Hayati, Ilda; Edyar, Busman (AL-ISTINBATH : Jurnal Hukum Islam, 2023)
This paper aims to analyze the position of Islamic law in the national legal system during the democratic transition (2001-2004), which was led by Megawati Sukarnoputri. Although she and the supporting party she led (PDIP) are often associated with secularism (at least considered insensitive to the problems of Muslims), during her reign from 2001 to 2004 several regulations were born that accommodated the interests of Muslims in the form of laws. This study uses a normative research method with primary-based secondary data sources. This study found that of the 126 laws that were legislated during the 2001-2004 transitional government, fourteen of them had intersections with the interests of Muslims which were accommodated in two patterns; first, formalist accommodation where the law strengthened the enactment of Islamic law for Muslims in Indonesia, such as Law No. 18 of 2001 concerning Special Autonomy for the Province of NAD; Law No. 18 of 2003 concerning Advocates, and so on. Second, accommodation in the form of substantive laws that are in line with Maqashid Shari'ah or at least do not contradict Islamic teachings as illustrated in Law No. 20 of 2001 concerning Amendments to Law No. 31 of 1999 concerning Corruption, Law No. 30 of 2002 concerning the Corruption Commission, Law No. 23 of 2002 concerning Child Protection, and others.